Utilizing Digital Virtual Reality Technology to Safeguard and Conserve Regional Indonesian Literature and Culture - Juwita, Ratna; Wijaya, Stefani Oktavia (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
Indonesian culture includes traditions, customs, visual arts, dance, music, culinary arts, architecture, and much more. Indonesia possesses unique literature and culture in various forms, such as poetry, prose, drama, and oral literature like folk tales and legends. The existing literature and culture are Indonesia's identity and cultural heritage that must be preserved. Digital Virtual Reality technology can serve as an effective medium by preserving culture in interactive forms, conserving traditions, presenting cultural performances, delivering cultural heritage with interactivity, and being globally accessible. This research utilizes a qualitative research method with a literature review approach. This method involves the analysis and interpretation of relevant literature sources, such as scholarly journals, books, articles, and papers related to the use of VR technology in preserving Indonesian regional literature and culture. By utilizing VR technology wisely, we can enhance accessibility, understanding, and appreciation of literature and culture worldwide, ensuring that this heritage continues to be valued and preserved for future generations.